Технології формування комунікативної компетенції - Романова, В.В. (Культура народов Причерноморья, 2013)
Стаття присвячена технолоіиям формуовання коммунікативної компетенції майбутніх
фахівців керувальної деятельності та несе мотиваціниый, когнитивно-процессуальний и аналітико-
корректирующий компоненти. Статья посвящена технологиям формирования коммуникативной компетенции
специалистов управленческой деятельности и включает мотивационный, когнитивно-процессуальный и
аналитико-корректирующий компоненты. The article presents the theoretical and experimental investigation of the problem of communicative
competence forming in future specialists of social and cultural activity. The essence of the notion
“communicative competence” is defined; the nature and structure of the communicative competence forming
technologies are substantiated. The criteria and indices revealing the level of its formation are worked out. The
main peculiarities of communicative competence are revealed. The program of integrative course
“communicative disciplines” is worked out and implemented in the teaching practice. The experiment results
confirm the efficiency of the technology of communicative competence forming in students of non-pedagogical
higher educational establishments.